2020
DOI: 10.1007/s00125-020-05096-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired counterregulatory responses to hypoglycaemia following oral glucose in adults with cystic fibrosis

Abstract: Aims/hypothesis The aim of this study was to determine the mechanism(s) for hypoglycaemia occurring late following oral glucose loading in patients with cystic fibrosis (CF). Methods A 3 h 75 g OGTT was performed in 27 non-diabetic adults with CF who were classified based on this test as experiencing hypoglycaemia (glucose <3.3 mmol/l with or without symptoms or glucose <3.9 mmol/l with symptoms, n = 14) or not (n = 13). Beta cell function, incretin (glucagon-like peptide-1 [GLP-1] and glucose-dependent insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 28 publications
(35 reference statements)
3
19
1
Order By: Relevance
“…Adrenaline was higher in the hypoglycemia group. Authors concluded that late hypoglycemia on OGTT was likely due to insufficient counterregulatory response rather than increased or delayed insulin secretion [27] . Overall these data suggest that both dysregulation in insulin secretion and impaired counterregulatory response to lowering glucose may contribute to postprandial hypoglycemia in CF.…”
Section: Spontaneous Hypoglycemia In Cfmentioning
confidence: 99%
“…Adrenaline was higher in the hypoglycemia group. Authors concluded that late hypoglycemia on OGTT was likely due to insufficient counterregulatory response rather than increased or delayed insulin secretion [27] . Overall these data suggest that both dysregulation in insulin secretion and impaired counterregulatory response to lowering glucose may contribute to postprandial hypoglycemia in CF.…”
Section: Spontaneous Hypoglycemia In Cfmentioning
confidence: 99%
“… 8 , 17 , 18 Insulin levels are lower in the first phase during an oral glucose tolerance test (OGTT) in CF and CFRD patients. 18 21 Also, there is an elevated secretion of proinsulin in both CFRD patients and CF patients with impaired glucose tolerance (IGT). 22 , 23 Failure to supress initial glucagon secretion following an OGTT correlates with decreased glucose tolerance among CF patients.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 99%
“… 29 Along the same lines, Kilberg et al 21 showed that reduced glucagon secretion hours after a meal can lead to hypoglycemic events in CF patients diagnosed with pancreatic insufficiency. The dysregulation of glucagon secretion, with impaired high secretion in the early post-prandial phase 20 , 24 followed by a failed counter-regulatory response in the later phase 20 , 30 is not well understood.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 99%
See 1 more Smart Citation
“…While basal and stimulated glucagon release is increased with acute pancreatitis [57], glucagon release is reduced in chronic pancreatitis, especially in the presence of diabetes [57,58]. In cystic fibrosis, glucagon release in response to arginine or following hypoglycaemia is reduced [40,42,59]. This defective glucagon release does not occur secondary to a loss of alpha cells.…”
Section: Islet Failure In Pancreatogenic Forms Of Diabetesmentioning
confidence: 99%